Manajemen Waktu Mahasiswa Pekerja dalam Menyeimbangkan Tanggung Jawab Akademik dan Pekerjaan Paruh Waktu - Rahmayani Hamid; Sri Fajriani; Muthia Nurul Hasanah; Nazhifa Putri Athifa; Chris Dayanti Br. Ginting (Contemporary Education Review, 2026)
Students who work part-time face significant challenges in managing their time, dividing their energy, and balancing academic and work demands. Imbalances in time management often lead to stress, fatigue, and a decline in academic performance. This article aims to analyze the time management strategies of working students through a study literature approach to research published between 2018 and 2024. The literature reviewed includes empirical and theoretical studies on self-regulation, time management, learning productivity, and the role balance of working students. The review results show that working students tend to use various strategies to manage their time, such as daily and weekly planning, prioritizing academic tasks, using time blocking techniques, and adjusting their learning rhythm based on their work schedule. In addition, the role of self-regulation was found to be a major factor that strengthens students' ability to monitor progress, control distractions, and maintain learning motivation despite their workload. The literature also emphasizes the importance of social support, academic flexibility, and the campus's understanding of the needs of working students. This article concludes that the success of working students in maintaining their academic performance is greatly influenced by a combination of time management strategies, self-regulation, and environmental support. These findings are expected to serve as a reference for educational institutions in designing more adaptive policies for working students.